Role of chronic stress and depression in periodontal diseases - Kimberly R. Warren; Teodor T. Postolache; Maureen Gröer; Omar F. Pinjari; Deanna L. Kelly; Mark A. Reynolds (2013)
Abstract An extensive body of experimental and clinical evidence documents the negative impact of chronic psychological stress and depression on the immune system and health. Chronic stress and depression can result in general dysregulation of the immune system, of both cellular and humoral pathways, which may contribute to pathogenic infection and concomitant periodontal tissue destruction. In general, the evidence is consistent with the hypothesis that stress can modify the host defense and progression of periodontal infections in patients susceptible to periodontitis. However, substantial evidence also indicates that these conditions can mediate risk for disease, including periodontitis, through changes in health‐related behaviors, such as oral hygiene, smoking and diet. The unequivocal interpretation of studies has also been hampered, in part, by issues related to conceptualization of stress and depression, as well as commonly associated comorbidities, such as diabetes, that can modify the onset and progression of periodontal disease. In addition, stress and depression appear to fall into a spectrum, ranging from mild to severe, involving a complex interaction of genetic background, coping strategies and environment. Differences in the conceptualization of stress and depression are probably important in assessing associations with other biologic and clinical measures. Future studies are necessary to clarify the complex interactions of chronic stress and depression in periodontal diseases.